The prevalence of chronic fatigue syndrome/ myalgic encephalomyelitis: a meta-analysis. - Johnston S.; Brenu E.W.; Staines D.; Marshall-Gradisnik S. (Clinical Epidemiology, 2013)
PURPOSE: To perform a meta-analysis to examine variability among prevalence estimates for CFS/ME, according to the method of assessment used. METHODS: Databases were systematically searched for studies on CFS/ME prevalence in adults that applied the 1994 Centers for Disease Control (CDC) case definition.1 Estimates were categorized into two methods of assessment: self-reporting of symptoms versus clinical assessment of symptoms. Meta-analysis was performed to pool prevalences by assessment using random effects modeling. This was stratified by sample setting (community or primary care) and heterogeneity was examined using the I (2) statistic. RESULTS: Of 216 records found, 14 studies were considered suitable for inclusion. The pooled prevalence for self-reporting assessment was 3.28% (95% CI: 2.24-4.33) and 0.76% (95% CI: 0.23-1.29) for clinical assessment. High variability was observed among self-reported estimates, while clinically assessed estimates showed greater consistency. CONCLUSION: The observed heterogeneity in CFS/ME prevalence may be due to differences in method of assessment. Stakeholders should be cautious of prevalence determined by the self-reporting of symptoms alone. The 1994 CDC case definition appeared to be the most reliable clinical assessment tool available at the time of these studies. Improving clinical case definitions and their adoption internationally will enable better comparisons of findings and inform health systems about the true burden of CFS/ME.